Preparation method of current collector, current collector, pole piece, secondary battery and electric equipment

By using polyacrylonitrile-coated carbon nanotube material as the current collector, the problem of easy disengagement of the positive electrode active material of zinc-manganese battery during charging and discharging is solved, and the effect of improving the reversible cycle capacity and stability of the battery is achieved.

CN119480879AActive Publication Date: 2025-02-18GUANGZHOU SECDES NEW ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411704795.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The lithium salt materials in lithium-ion batteries are costly and have a safety hazard for organic electrolytes. The positive electrode active material of secondary zinc-manganese battery is easily separated from the current collector and dissolved in the electrolyte during charging and discharging, resulting in a reduction in the battery's reversible circulation capacity and impacting the stability of the battery. .

Method used

Polyacrylonitrile-coated carbon nanotube material is used as the current collector, and a carbon coating with rich pore structure is formed by carbonization treatment, providing rich adhesion sites to inhibit the shedding of the active material and improve conductivity.

Benefits of technology

The reversible cycle capacity and electrode structure of the positive electrode of the zinc-manganese battery are improved, and the adhesion and conductivity of the active material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480879A_ABST
    Figure CN119480879A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a current collector, the current collector, a pole piece, a secondary battery and electric equipment. The preparation method comprises the following steps: dissolving polyacrylonitrile in a solvent, and mixing carbon nanotubes with the formed polyacrylonitrile solution to form mixed slurry; removing the solvent in the mixed slurry to form a polyacrylonitrile coated carbon nanotube material; and carrying out carbonization treatment on the polyacrylonitrile coated carbon nanotube material, wherein the temperature of the carbonization treatment is 800 DEG C or above. The current collector prepared by the preparation method can provide abundant attachment sites for an active material, and particles of the active material are prevented from falling off from the current collector, so that the reversible cycle capacity of the battery is improved, and the stability of an electrode structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a current collector, a current collector, a pole piece, a secondary battery and electrical equipment. Background Art

[0002] The most widely used secondary battery in commercial applications is the lithium-ion battery. Lithium-ion batteries usually require lithium salts and organic electrolytes. The material cost of lithium salts is relatively high, which leads to the high production cost of lithium-ion batteries. Organic electrolytes are easily decomposed in the air, which poses a great safety hazard. Compared with lithium-ion batteries, rechargeable secondary zinc-manganese batteries have lower material costs and can use aqueous electrolytes to conduct ions, so they also have higher safety and higher ionic conductivity.

[0003] Secondary zinc-manganese batteries usually use materials such as manganate and manganese oxide as positive electrode active materials. In secondary zinc-manganese batteries using aqueous electrolytes, the positive electrode active materials will gradually detach from the current collector and dissolve in the electrolyte during the charge and discharge process, which will not only significantly reduce the reversible cycle capacity of the battery, but also affect the stability of the battery. Summary of the invention

[0004] Based on this, it is necessary to provide a method for preparing a current collector to address the problems in the above-mentioned background technology, and the current collector prepared by the method can effectively improve the reversible cycle capacity of the positive electrode active material.

[0005] In a first aspect, according to some embodiments of the present disclosure, a method for preparing a current collector is provided, which comprises the following steps:

[0006] dissolving polyacrylonitrile in a solvent, and mixing the carbon nanotubes with the formed polyacrylonitrile solution to form a mixed slurry;

[0007] removing the solvent in the mixed slurry to form a polyacrylonitrile-coated carbon nanotube material; and,

[0008] The polyacrylonitrile-coated carbon nanotube material is subjected to carbonization treatment at a temperature above 800°C.

[0009] In some embodiments of the present disclosure, after the polyacrylonitrile-coated carbon nanotube material is carbonized, the specific surface area of ​​the formed carbonized material is ≥50m 2 / g; and / or, the pore volume of the formed carbonized material is ≥0.2cm 3 / g; and / or, the average pore size of the formed carbonized material is ≥5nm.

[0010] In some embodiments of the present disclosure, in the mixed slurry, the mass ratio of the polyacrylonitrile to the carbon nanotubes is 1:(4~29).

[0011] In some embodiments of the present disclosure, in the polyacrylonitrile-coated carbon nanotube material, the mass proportion of the carbon nanotube is 80% to 96.7%, and the mass proportion of the polyacrylonitrile is 3.3% to 20%.

[0012] In some embodiments of the present disclosure, before the polyacrylonitrile-coated carbon nanotube material is carbonized, the following steps are also included: placing the polyacrylonitrile-coated carbon nanotube material in a gas environment containing oxygen for annealing; during the annealing process, heating the polyacrylonitrile-coated carbon nanotube material to 150°C~250°C, keeping it warm for 1h~2h, and then cooling it naturally.

[0013] In some embodiments of the present disclosure, the carbonization process of the polyacrylonitrile-coated carbon nanotube material is carried out in a protective gas, and the carbonization time is 1 hour to 4 hours.

[0014] In some embodiments of the present disclosure, before the polyacrylonitrile coated carbon nanotube material is carbonized, the following step is further included: placing the polyacrylonitrile coated carbon nanotube material in an oxidant containing nitric acid to perform a pre-oxidation treatment on the polyacrylonitrile coated carbon nanotube material.

[0015] In some embodiments of the present disclosure, before removing the solvent in the mixed slurry, the step of coating the mixed slurry on a surface of a conductive substrate to form a coating layer is also included.

[0016] In a second aspect, the present disclosure further provides a current collector, which is prepared by the method for preparing the current collector according to the above embodiment.

[0017] In a third aspect, the present disclosure further provides a pole piece, which includes an active material layer and a current collector according to the above embodiment, wherein the active material layer is disposed on the current collector.

[0018] In some embodiments of the present disclosure, the active material layer includes a manganese-based material.

[0019] In a fourth aspect, the present disclosure further provides a secondary battery, the secondary battery comprising a positive electrode and a negative electrode arranged opposite to each other, the positive electrode and / or the negative electrode comprising a pole piece as described in any of the above embodiments.

[0020] In a fifth aspect, the present disclosure further provides an electrical device, which includes a functional body and a secondary battery as described in any of the above embodiments, wherein the secondary battery is used to supply power to the functional body.

[0021] In the preparation method of the current collector disclosed in the present invention, polyacrylonitrile is first dissolved in a solvent and carbon nanotubes are added. A plurality of carbon nanotubes are staggered to form a conductive skeleton, and there are abundant gaps between the staggered carbon nanotubes. After removing the solvent, polyacrylonitrile can be coated on the surface of the carbon nanotube skeleton. The polyacrylonitrile coating layer undergoes pyrolysis and carbonization during the carbonization treatment at above 800°C, and a carbon coating layer having a large number of holes with moderate pore sizes is formed on the basis of the gaps in the carbon nanotube skeleton. The current collector prepared by this preparation method can provide abundant attachment sites for the active material, inhibit the particles of the active material from falling off the current collector, thereby improving the reversible cycle capacity of the battery and improving the stability of the electrode structure.

[0022] The current collector is particularly suitable for the positive electrode of aqueous zinc-manganese batteries. Specifically, since the surface formed after carbonization has rich and complex mesopores and macropore structures, it can be used to accommodate particles of manganese-based active materials and inhibit the particles of active materials from falling off. At the same time, the carbon coating layer in the current collector is used as a conductive attachment site, and the carbon nanotubes are used as a conductive skeleton therein, which can effectively promote the transmission of electrons from the active material to the current collector, thereby improving the problem of poor conductivity of the active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the steps of a method for preparing a current collector according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0024] To facilitate understanding of the present invention, a more comprehensive description of the present invention is provided below. The preferred embodiments of the present invention are given herein. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the content of the present invention more thorough and comprehensive.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this document pertains. The terms used herein in the specification of this document are only for describing specific embodiments and are not intended to limit this document.

[0026] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be a limitation of the present disclosure. When used herein, the singular forms "a", "an" and "the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0027] The present disclosure provides a method for preparing a current collector, which includes the following steps: dissolving polyacrylonitrile in a solvent and adding carbon nanotubes into the solvent to form a mixed slurry; coating the mixed slurry on a conductive substrate, and removing the solvent in the mixed slurry to form a coating layer on the conductive substrate; and carbonizing the polyacrylonitrile in the coating layer at a temperature of above 800°C.

[0028] In the preparation method of the current collector disclosed in the present invention, polyacrylonitrile is first dissolved in a solvent and carbon nanotubes are added. A plurality of carbon nanotubes are staggered to form a conductive skeleton, and there are abundant gaps between the staggered carbon nanotubes. After removing the solvent, polyacrylonitrile can be coated on the surface of the carbon nanotube skeleton. The polyacrylonitrile coating layer undergoes pyrolysis and carbonization during the carbonization treatment, and a carbon coating layer having a large number of holes with moderate pore sizes is formed on the basis of the gaps in the carbon nanotube skeleton. The current collector prepared by this preparation method can provide abundant attachment sites for the active material, inhibit the particles of the active material from falling off the current collector, thereby improving the reversible cycle capacity of the battery and improving the stability of the electrode structure.

[0029] The current collector is particularly suitable for the positive electrode of aqueous zinc-manganese batteries. Specifically, due to the rich and complex pore structure on the surface formed after carbonization, it can be used to accommodate particles of manganese-based active materials and inhibit the particles of active materials from falling off. At the same time, the carbon coating layer in the current collector is used as a conductive attachment site, and the carbon nanotubes are used as a conductive skeleton, which can effectively promote the transmission of electrons from the active material to the current collector, thereby improving the problem of poor conductivity of the active material.

[0030] Figure 1 Schematic diagram of the steps of a method for preparing a current collector disclosed in the present invention. Figure 1 As shown, the preparation method of the current collector includes steps S1 to S3, which are specifically as follows.

[0031] Step S1, dissolving polyacrylonitrile in a solvent, and mixing carbon nanotubes with the formed polyacrylonitrile solution to form a mixed slurry.

[0032] As an example of this embodiment, the molecular weight of polyacrylonitrile is 50,000-300,000, which is conducive to forming a denser and more uniform coating layer.

[0033] It is understood that the solvent should be selected from a solvent capable of dissolving polyacrylonitrile. As an example of this embodiment, the solvent may include an organic solvent, and the organic solvent is selected from dimethyl sulfoxide. Further, the solvent may also include water, that is, the solvent may be a mixture of an organic solvent and water.

[0034] As an example of this embodiment, the step of dissolving polyacrylonitrile in a solvent includes: adding polyacrylonitrile to the solvent, heating the solvent, and stirring the solvent.

[0035] In some examples, when the solvent is heated, the temperature of the solvent is controlled to be 80° C. to 120° C.

[0036] As an example of this embodiment, after polyacrylonitrile is dissolved in a solvent, the mass concentration of polyacrylonitrile may be 0.005 g / mL to 0.05 g / mL. This mass concentration of polyacrylonitrile is conducive to forming a coating layer with a relatively uniform thickness on the surface of the carbon nanotubes.

[0037] As an example of this embodiment, in the step of mixing the carbon nanotubes with the formed polyacrylonitrile solution, a dispersion containing the carbon nanotubes may be mixed with the formed polyacrylonitrile solution to promote sufficient dispersion of the carbon nanotubes in the polyacrylonitrile solution.

[0038] In some examples, the method of preparing the dispersion containing carbon nanotubes includes: mixing the aqueous carbon nanotube dispersion with an organic solvent and then performing a heating treatment.

[0039] In some examples, the organic solvent used in mixing the aqueous carbon nanotube dispersion with the organic solvent is the same as the organic solvent in the polyacrylonitrile solution.

[0040] In some examples, in the aqueous carbon nanotube dispersion, the solid content of the carbon nanotubes may be 2% to 8%.

[0041] In some examples, in the step of mixing the aqueous carbon nanotube dispersion with the organic solvent, the mass ratio of the aqueous carbon nanotube dispersion to the organic solvent is (1-8):1.

[0042] In some examples, during the heating process after mixing the aqueous carbon nanotube dispersion with the organic solvent, the heating temperature can be controlled to be 100° C. to 140° C., and the heating time can be controlled to be 1 h to 4 h to promote sufficient mixing of the aqueous carbon nanotube dispersion with the organic solvent.

[0043] As an example of this embodiment, in the mixed slurry, the mass ratio of polyacrylonitrile to carbon nanotubes is 1: (4-29). Among them, the mass of carbon nanotubes is much greater than that of polyacrylonitrile, mainly because carbon nanotubes are used as the main matrix structure and polyacrylonitrile is used to form a thinner coating layer, so that abundant mesopores and macropores can be formed during the carbonization process. Using polyacrylonitrile and carbon nanotubes in this mass ratio as raw materials is conducive to obtaining a carbonized material with a large pore volume and an average pore size.

[0044] In some examples, the mass ratio of polyacrylonitrile to carbon nanotubes can be 1:4, 1:6, 1:8, 1:10, 1:12, 1:15, 1:20, 1:25, 1:29, or the mass ratio of polyacrylonitrile to carbon nanotubes can be between any two of the above mass ratios.

[0045] As an example of this embodiment, the step of mixing the carbon nanotubes with the formed polyacrylonitrile solution includes: mixing the dispersion containing the carbon nanotubes with the polyacrylonitrile solution, and then heating and stirring the mixture.

[0046] In the step of heating and stirring, the heating temperature may be 30° C. to 50° C., and stirring may be continued for 1 h to 2 h during the heating process.

[0047] After the above step S1, a mixed slurry in which carbon nanotubes and polyacrylonitrile are uniformly dispersed can be formed.

[0048] Step S2, removing the solvent in the mixed slurry to form a polyacrylonitrile-coated carbon nanotube material.

[0049] As an example of this embodiment, the method of removing the solvent in the mixed slurry may be drying, such as freeze drying or baking.

[0050] It can be understood that in this embodiment, the mixed slurry can be first applied to the support material to form a coating layer on the surface of the support material. Further, as an example of this embodiment, before removing the solvent in the mixed slurry, the mixed slurry is also applied to the surface of the conductive substrate to form a coating layer.

[0051] As a further example of this embodiment, after forming the coating layer, the conductive substrate with the coating layer may be placed in a forced air oven to evaporate the solvent in the coating layer, so that the coating layer forms a polyacrylonitrile-coated carbon nanotube material.

[0052] Among them, the temperature of the blast oven can be set to 60℃~100℃.

[0053] As a further example of this embodiment, after removing the solvent from the mixed slurry, the polyacrylonitrile-coated carbon nanotube material can be washed in ethanol and deionized water in turn to remove impurities therein, and then dried in a blast oven.

[0054] As an example of this embodiment, the polyacrylonitrile-coated carbon nanotube material contains only carbon nanotubes and polyacrylonitrile except for impurities.

[0055] As a further example of this embodiment, in the polyacrylonitrile-coated carbon nanotube material, the mass proportion of the carbon nanotube is 80% to 96.7%. For example, the mass proportion of the carbon nanotube can be 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96.7%, or the mass proportion of the carbon nanotube can also be between any two of the above mass proportions.

[0056] As a further example of this embodiment, in the polyacrylonitrile-coated carbon nanotube material, the mass proportion of polyacrylonitrile is 3.3% to 20%. For example, the mass proportion of polyacrylonitrile can be 3.3%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, or the mass proportion of polyacrylonitrile can also be between any two of the above mass proportions.

[0057] As a further example of this embodiment, the conductive substrate is selected from carbon cloth, carbon paper, stainless steel mesh, stainless steel foil, titanium mesh, titanium foil or nickel foam. It can be understood that the conductive substrate and the carbonized polyacrylonitrile-coated carbon nanotube material as a whole can serve as a current collector.

[0058] Step S3, carbonizing the polyacrylonitrile-coated carbon nanotube material.

[0059] As an example of this embodiment, before the carbonization treatment is performed on the polyacrylonitrile-coated carbon nanotube material, the following step is further included: placing the polyacrylonitrile-coated carbon nanotube material in an oxidant containing nitric acid to perform a pre-oxidation treatment on the coating layer.

[0060] Among them, the pre-oxidation treatment can remove some reducing impurities remaining in the material. More importantly, the pre-oxidation treatment can also oxidize the surface of polyacrylonitrile and carbon nanotubes and cause defects on the surface of the polyacrylonitrile coating layer, which is conducive to increasing the number of mesopores and mesopores generated in the subsequent calcination process.

[0061] As a further example of this embodiment, the nitric acid may be concentrated nitric acid, in which the mass concentration of nitric acid is above 50%.

[0062] As a further example of this embodiment, the polyacrylonitrile-coated carbon nanotube material is immersed in the oxidant for 20 minutes to 60 minutes.

[0063] As an example of this embodiment, before the carbonization treatment is performed on the polyacrylonitrile-coated carbon nanotube material, the following step is further included: placing the polyacrylonitrile-coated carbon nanotube material in a gas environment containing oxygen for annealing treatment.

[0064] As a further example of this embodiment, annealing can be performed after pre-oxidation. Pre-oxidation can cause certain defects on the surface of polyacrylonitrile, and the subsequent annealing can further decompose the polyacrylonitrile, so that a certain microporous structure is formed on the surface of polyacrylonitrile before carbonization, and the microporous structure will expand and form abundant mesopores and mesopores during the subsequent calcination process. In addition, the annealing process can also make the structure of polyacrylonitrile coated carbon nanotubes more stable, which is conducive to ensuring the stable combination between the formed carbon coating layer and the carbon nanotubes during the subsequent carbonization process.

[0065] As a further example of this embodiment, during the annealing process, the polyacrylonitrile-coated carbon nanotube material is heated to 150° C. to 250° C., kept at this temperature for 1 h to 2 h, and then cooled naturally.

[0066] The step of carbonization treatment may be performed after the step of annealing treatment. As an example of this embodiment, the process of carbonization treatment of polyacrylonitrile-coated carbon nanotube material is performed in a protective gas. The protective gas may be selected from at least one of argon and nitrogen.

[0067] In this embodiment, the temperature of the carbonization treatment is above 800° C. As an example of this embodiment, during the carbonization treatment, the temperature of the carbonization treatment is 800° C. to 1300° C.

[0068] The carbonization process can produce a large number of nano-scale pores on the surface of polyacrylonitrile. The number of these pores is correlated with the temperature of the carbonization treatment. When the temperature is low, the carbonization rate is slow and the degree of carbonization is low, resulting in a significantly smaller number of micropores. In general, setting the carbonization temperature to 800℃~1300℃ is conducive to obtaining a carbon coating with a large number of micropores.

[0069] As an example of this embodiment, during the carbonization process, the carbonization time is 1 hour to 4 hours.

[0070] As an example of this embodiment, after the polyacrylonitrile-coated carbon nanotube material is carbonized, the specific surface area of ​​the formed carbonized material is ≥50m 2 / g.

[0071] As a further example of this embodiment, after the polyacrylonitrile-coated carbon nanotube material is carbonized, the specific surface area of ​​the formed carbonized material is 50 m 2 / g~500m 2 / g.

[0072] As an example of this embodiment, the pore volume of the carbonized material formed is ≥ 0.2 cm 3 / g.

[0073] As a further example of this embodiment, after the polyacrylonitrile-coated carbon nanotube material is carbonized, the pore volume of the formed carbonized material is 0.2 cm 3 / g~1cm 3 / g.

[0074] As an example of this embodiment, the carbonized material is formed to have an average pore size of ≥5 nm.

[0075] As a further example of this embodiment, after the polyacrylonitrile-coated carbon nanotube material is carbonized, the average pore size of the formed carbonized material is 5 nm to 20 nm.

[0076] After steps S1 to S3, the method for preparing the current collector disclosed in the present invention can be completed.

[0077] In a second aspect, the present disclosure further provides a current collector, which is prepared by the above-mentioned current collector preparation method. The current collector is particularly suitable for use in aqueous zinc-manganese batteries, and as a positive electrode current collector in aqueous zinc-manganese batteries, it can effectively solve the problems of pulverization and shedding of positive electrode materials and poor conductivity.

[0078] In a third aspect, the present disclosure further provides a pole piece, which comprises an active material layer and a current collector as in the above embodiment. The active material layer is disposed on the current collector.

[0079] As an example of this embodiment, the active material layer includes a positive electrode active material, and the positive electrode active material includes a manganese-based compound.

[0080] As a further example of this embodiment, the manganese-based compound includes one or more of manganate and manganese oxide, wherein the manganate may include but is not limited to one or more of lithium manganate and nickel manganate, and the manganese oxide may include but is not limited to manganese dioxide.

[0081] As an example of this embodiment, the positive electrode active material may be formed into a positive electrode active layer by electrodeposition or coating.

[0082] In a fourth aspect, the present disclosure further provides a secondary battery, the secondary battery comprising a positive electrode and a negative electrode arranged opposite to each other, the positive electrode and / or the negative electrode comprising a pole piece as in the above embodiment.

[0083] As an example of this embodiment, the secondary battery may be a zinc-manganese battery. In other examples, the secondary battery may also be, but is not limited to, one of a lithium-ion battery, a lithium metal battery, a lithium-air battery, and a zinc-air battery.

[0084] As an example of this embodiment, the secondary battery is a zinc-manganese battery, and the electrolyte in the zinc-manganese battery is an aqueous electrolyte. It can be understood that the solvent in the aqueous electrolyte includes water, and the solute in the aqueous electrolyte includes an electrolyte salt.

[0085] As a further example of this embodiment, the electrolyte in the aqueous electrolyte may include one or more of zinc sulfate and manganese sulfate.

[0086] As a further example of this embodiment, in the secondary battery, the negative electrode may include one or more of metallic zinc and a zinc alloy.

[0087] In a fifth aspect, the present disclosure further provides an electric device, which includes a functional body and a secondary battery as described in the above embodiment, wherein the secondary battery is used to supply power to the functional body.

[0088] As some examples of this embodiment, the power-consuming device may be a mobile phone, a laptop computer, a smart watch, an electric car, a medical device, a portable charging station, a spaceflight device, a smart home, or an energy storage power station. The energy storage power station may be a photovoltaic energy storage power station, a wind power energy storage power station, a hydropower energy storage power station, a thermal power energy storage power station, etc.

[0089] The present disclosure also provides the following more specific embodiments and comparative examples.

[0090] Example 1

[0091] Prepare mixed slurry: Take 0.8g of polyacrylonitrile and add it to 8mL of dimethyl sulfoxide, then add 2mL of deionized water, stir magnetically and heat to 120℃ to completely dissolve it to form a polyacrylonitrile solution. Add the aqueous carbon nanotube dispersion (wherein the solid content of carbon nanotubes is 5%) to dimethyl sulfoxide, mix the aqueous carbon nanotube dispersion and dimethyl sulfoxide in a mass ratio of 1:5, heat to 120℃ and keep warm for 2h to form a carbon nanotube dispersion. Mix the prepared polyacrylonitrile solution and carbon nanotube dispersion evenly, heat to 40℃ and stir for 2h to form a mixed slurry. The mass ratio of polyacrylonitrile to carbon nanotubes is 1:15.

[0092] Preparation of polyacrylonitrile-coated carbon nanotube material: The mixed slurry is coated on the surface of the carbon cloth to form a coating layer, and then placed in a blast oven at 80°C to dry to form a polyacrylonitrile-coated carbon nanotube material. Then, it is soaked in ethanol for 10 minutes, rinsed with deionized water, and then placed in a blast oven at 80°C to dry for use.

[0093] Preparation of carbon-coated carbon nanotube material: The carbon arrangement formed with the polyacrylonitrile-coated carbon nanotube material is soaked in concentrated nitric acid for 30 minutes for pre-oxidation treatment, and then rinsed with deionized water and placed in a blast oven at 80°C for drying. The pre-oxidation polyacrylonitrile-coated carbon nanotube material is transferred to a tubular furnace, heated to 200°C in air, kept warm for 2 hours, and then naturally cooled for annealing. After annealing, argon gas is introduced into the tubular furnace, heated to 900°C, kept warm for 3 hours, and then naturally cooled to complete the carbonization treatment and form a carbon-coated carbon nanotube material.

[0094] Example 2

[0095] Example 2 is substantially the same as Example 1, except that in the mixed slurry, the mass ratio of polyacrylonitrile to carbon nanotubes is 1:4.

[0096] Example 3

[0097] Example 3 is substantially the same as Example 1, except that in the mixed slurry, the mass ratio of polyacrylonitrile to carbon nanotubes is 1:2.

[0098] Example 4

[0099] Example 4 is substantially the same as Example 1, except that in the mixed slurry, the mass ratio of polyacrylonitrile to carbon nanotubes is 1:29.

[0100] Example 5

[0101] Example 5 is substantially the same as Example 1, except that in the mixed slurry, the mass ratio of polyacrylonitrile to carbon nanotubes is 1:39.

[0102] Example 6

[0103] Example 6 is basically the same as Example 1, with the only difference being that after the annealing treatment, argon gas is introduced into the tubular furnace, the temperature is raised to 800° C. and maintained for 3 hours, and then naturally cooled to complete the carbonization treatment to form a carbon-coated carbon nanotube material.

[0104] Example 7

[0105] Example 7 is basically the same as Example 1, except that after the annealing treatment, argon gas is introduced into the tube furnace, the temperature is raised to 1100° C. and kept for 3 hours, and then naturally cooled to complete the carbonization treatment to form a carbon-coated carbon nanotube material.

[0106] Example 8

[0107] Example 8 is basically the same as Example 1, except that in the process of preparing the carbon-coated carbon nanotube material, neither pre-oxidation treatment nor annealing treatment is performed, and carbonization treatment is directly performed.

[0108] Example 9

[0109] Example 9 is basically the same as Example 1, except that in the process of preparing the carbon-coated carbon nanotube material, the carbonization treatment is directly performed after the pre-oxidation treatment without annealing treatment.

[0110] Example 10

[0111] Example 10 is substantially the same as Example 1, with the only difference being that in the process of preparing the carbon-coated carbon nanotube material, no pre-oxidation treatment is performed, and the carbonization treatment is performed directly after the annealing treatment.

[0112] Comparative Example 1

[0113] Comparative Example 1 is substantially the same as Example 1, except that no carbon nanotube slurry is added, and the carbon material is directly prepared using polyacrylonitrile solution.

[0114] Comparative Example 2

[0115] Comparative Example 2 is substantially the same as Example 1, except that the temperature of the carbonization treatment is 600°C.

[0116] Comparative Example 3

[0117] Carbon nanotubes, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1 to form a slurry, which was then coated on the surface of the carbon cloth and dried in a forced air oven at 80° C. to serve as a current collector.

[0118] Experiment 1: The specific surface area (S) of the carbon materials prepared in each embodiment and comparative example was measured by the BET method. BET ), total pore volume (V) and average pore diameter (D), the total pore volume includes the pore volume of micropores with a pore diameter less than 2nm and the pore volume of mesopores with a pore diameter greater than 2nm. The test results are shown in Table 1.

[0119] Experiment 2: The four-probe method was used to test the square resistance of the surface carbon material layer in the current collector prepared in each embodiment and comparative example. The test results are shown in Table 1.

[0120] Test 3: Manganese dioxide powder was formed on the surface of the current collector of each embodiment and comparative example by coating as the positive electrode. Zinc foil was used as the negative electrode. Glass fiber membrane was used as the diaphragm. An aqueous solution dissolved with zinc sulfate (ZnSO4) and manganese sulfate (MnSO4) was used as the electrolyte, wherein the molar concentration of zinc sulfate was 2 mol / L, and the molar concentration of manganese sulfate was 0.1 mol / L. The above-mentioned positive electrode, negative electrode, diaphragm and electrolyte were assembled to form an aqueous zinc-manganese battery. Using the Xinwei battery test system, 100 charge and discharge cycles were performed under a constant current of 0.1 A / g. The first-cycle discharge specific capacity and the discharge specific capacity after 100 cycles of each embodiment and comparative example were recorded, and the capacity retention rate was calculated accordingly. The results can be seen in Table 2.

[0121] Table 1

[0122]

[0123] As shown in Table 1, the carbon materials prepared in Examples 1 to 10 all have large specific surface areas and large pore volumes. Among them, the specific surface area of ​​the carbon material prepared in Example 1 can reach 150.4 m 2 / g, which is conducive to more complete contact with the active material. In addition, the carbon material has a low square resistance, which is also conducive to sufficient conduction of electrons. More importantly, the carbon material prepared in Example 1 has a pore volume of 0.515cm 3 / g while still maintaining a pore size of 13.09nm, indicating that it contains a large number of large-sized mesopores and mesopores. This is conducive to the carbon material to accommodate and fix the particles of the active material to avoid falling off. Compared with Examples 1 to 10, Comparative Example 1 did not use carbon nanotubes, but only used polyacrylonitrile solution as a raw material. The specific surface area, pore volume and pore size of Comparative Example 1 were significantly lower than those of Examples 1 to 10. Its pore volume was extremely small and all were micropores of about 2nm. This shows that in the absence of the support of carbon nanotubes, it is difficult for a single polyacrylonitrile to form a large number of mesopores and mesopores during the carbonization process, and it also shows that the presence of carbon nanotubes plays a key role in the formation of porous structures. The temperature of the carbonization treatment of Comparative Example 2 is only 600°C. At this temperature, although polyacrylonitrile can be carbonized and has a large pore size, the pore volume is very low. It is speculated that this is mainly because the lower temperature leads to a slower carbonization rate of polyacrylonitrile, which causes polyacrylonitrile to have sufficient time to slowly deform when heated, which is not conducive to the formation of a large number of mesopores and mesopores.

[0124] Compared with Example 1, the proportion of polyacrylonitrile in Example 2 and Example 3 is successively reduced, which results in that the surface of carbon nanotubes is not easily uniformly coated by polyacrylonitrile during the preparation process, and then the pore structure generated during the carbonization process is reduced. Therefore, the specific surface area, pore volume and pore diameter of Example 2 and Example 3 are all lower than those of Example 1. In addition, the pore volume and pore diameter of Example 3 have decreased significantly, which indicates that when the content of polyacrylonitrile is too low, the number of pores in the carbon material will be reduced. The proportion of polyacrylonitrile in Example 4 and Example 5 increases successively, which results in that the carbon nanotubes as the skeleton in the final carbon material are too few, and polyacrylonitrile lacks the support of carbon nanotubes, which is not conducive to the formation of pores with larger pore diameters. Therefore, the pore volume and pore diameter of Example 4 and Example 5 are both lower than those of Example 1. In addition, the specific surface pore diameter of Example 5 has decreased significantly, indicating that when the content of polyacrylonitrile is too high, the pore size of the carbon material will also be significantly reduced.

[0125] Compared with Example 1, the carbonization temperatures of Example 6 and Example 7 are 800°C and 1100°C respectively. The specific surface area and pore volume of Example 6 are slightly lower than those of Example 1, and the specific surface area and pore volume of Example 7 are similar to those of Example 1. This indicates that when the carbonization temperature is above 800°C, polyacrylonitrile can be quickly and fully decomposed during the carbonization process, thereby producing a rich porous structure in the carbon material.

[0126] Compared with Example 1, Example 8 was not subjected to pre-oxidation and annealing, Example 9 was only subjected to pre-oxidation, and Example 10 was only subjected to annealing, and its specific surface area, pore volume and pore size were significantly lower than those of Example 1. Among them, compared with Example 8, the specific surface area, pore volume and pore size of Example 9 were all increased, mainly because the pre-oxidation treatment can form defects on the surface of polyacrylonitrile, and these defects can be used as sites for pore generation during the subsequent calcination process. The specific surface area, pore volume and pore size of Example 10 were all reduced, mainly because the annealing process made the surface of polyacrylonitrile smoother, which is not conducive to the generation of holes. In addition, compared with Example 9, the specific surface area, pore volume and pore size of Example 1, which was annealed after pre-oxidation, were greatly improved, which shows that the two steps of pre-oxidation and annealing have a synergistic effect in obtaining a richer porous structure and increasing the specific surface area and pore volume of carbon materials. It is speculated that this phenomenon is mainly caused by the annealing process promoting the deformation of the defective areas formed during the pre-oxidation process into depressions, and then a large number of mesoporous and mesoporous structures are generated based on the depressions during the calcination process.

[0127] Table 2

[0128]

[0129] Further, please refer to the contents shown in Table 2. Examples 1 to 10 all show a first-cycle discharge capacity of more than 275 mAh / g and a capacity retention rate of more than 90%. This is mainly because the pore volume and average pore size of the carbon materials in Examples 1 to 10 are relatively large, which provides abundant attachment sites for the active material and inhibits the shedding of manganese dioxide powder. Among them, the carbon material with a larger specific surface area can ensure the full charge and discharge of the active material. In contrast, although Comparative Example 1 also has a certain specific surface area, there are no carbon nanotubes as a skeleton support, and the pore volume and average pore size are extremely low, which makes it difficult to accommodate the active material, resulting in the active material still easily falling off the current collector, so its cycle capacity retention rate is significantly lower than that of Examples 1 to 10. Although the carbon material in Comparative Example 2 has a larger average pore size, the pore volume is very small and it is also difficult to accommodate the active material. And its conductivity is significantly poor, which makes it difficult for the active material to be effectively and fully discharged, so the first-cycle discharge capacity and capacity retention rate of the carbon material in Comparative Example 2 are even lower than those in Comparative Example 1. In Comparative Example 3, a conductive coating was prepared on the surface of the carbon cloth, which also resulted in a large amount of manganese dioxide powder falling off during the charge and discharge cycle, and showed an extremely low charge and discharge specific capacity after 50 cycles.

[0130] From the above, it can be seen that the current collector prepared by the preparation method of the present invention can provide abundant attachment sites for the active material, inhibit the particles of the active material from falling off from the current collector, thereby improving the reversible cycle capacity of the battery and improving the stability of the electrode structure.

[0131] It should be understood that, unless otherwise specified herein, there is no strict order restriction for the execution of the steps, and the steps may be executed in other orders. Moreover, at least a portion of the steps in the preparation process may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but may be executed at different times, and the execution order of these sub-steps or stages is not necessarily sequential.

[0132] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A method for preparing a current collector, characterized in that: The steps include: dissolving polyacrylonitrile in a solvent, and mixing the carbon nanotubes with the formed polyacrylonitrile solution to form a mixed slurry; removing the solvent in the mixed slurry to form a polyacrylonitrile-coated carbon nanotube material; as well as, The polyacrylonitrile-coated carbon nanotube material is subjected to carbonization treatment at a temperature above 800°C.

2. The method for preparing a current collector according to claim 1, characterized in that: After the polyacrylonitrile-coated carbon nanotube material is carbonized, the specific surface area of ​​the formed carbonized material is ≥50m 2 / g; and / or, the pore volume of the formed carbonized material is ≥0.2cm 3 / g; and / or, the average pore size of the formed carbonized material is ≥5nm.

3. The method for preparing a current collector according to claim 2, characterized in that: In the mixed slurry, the mass ratio of the polyacrylonitrile to the carbon nanotubes is 1:(4-29).

4. The method for preparing a current collector according to claim 3, characterized in that: In the polyacrylonitrile-coated carbon nanotube material, the mass proportion of the carbon nanotube is 80% to 96.7%, and the mass proportion of the polyacrylonitrile is 3.3% to 20%.

5. The method for preparing a current collector according to any one of claims 1 to 4, characterized in that: Before the carbonization treatment is performed on the polyacrylonitrile-coated carbon nanotube material, the following steps are also included: placing the polyacrylonitrile-coated carbon nanotube material in a gas environment containing oxygen for annealing treatment; During the annealing process, the polyacrylonitrile-coated carbon nanotube material is heated to 150° C. to 250° C., kept at this temperature for 1 h to 2 h, and then cooled naturally; and / or, The carbonization process of the polyacrylonitrile-coated carbon nanotube material is carried out in a protective gas, and the carbonization time is 1 hour to 4 hours.

6. The method for preparing a current collector according to any one of claims 1 to 4, characterized in that: Before the polyacrylonitrile coated carbon nanotube material is subjected to carbonization treatment, the method further comprises the following steps: placing the polyacrylonitrile coated carbon nanotube material in an oxidant to perform a pre-oxidation treatment on the polyacrylonitrile coated carbon nanotube material.

7. The method for preparing a current collector according to any one of claims 1 to 4, characterized in that: Before removing the solvent in the mixed slurry, the method further includes coating the mixed slurry on the surface of a conductive substrate to form a coating layer.

8. A current collector, characterized in that: The current collector is prepared by the method for preparing the current collector according to any one of claims 1 to 7.

9. A pole piece, characterized in that: The invention comprises an active material layer and the current collector according to claim 8, wherein the active material layer is disposed on the current collector.

10. The pole piece according to claim 9, characterized in that: The active material layer includes a manganese-based material.

11. A secondary battery, characterized in that: The secondary battery comprises a positive electrode and a negative electrode arranged opposite to each other, and the positive electrode and / or the negative electrode comprises the electrode sheet as claimed in any one of claims 9 to 10.

12. An electrical device, characterized in that: The invention comprises a functional body and the secondary battery according to claim 11, wherein the secondary battery is used to supply power to the functional body.

Citation Information

Patent Citations

  • Preparation method for polyacrylonitrile-based carbon fiber

    CN102953152A

  • Preparation and application of porous carbon coated orientation carbon nano tube / sulfur composite anode

    CN104362290A

  • Preparation method of anti-lithium dendritic crystal lithium metal battery anode side interlayer material

    CN111900373A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN118978160A

  • Preparation method of polyacrylonitrile-carbon nanotube composite and the composite thereby

    KR1020120071522A